Psychological determinants of loneliness in adolescence (Actual Problems of Psychology in Educational Institutions, 2022)
The article is devoted to the problem of solitude in adolescence. Some psychological determinants of loneliness are identified and analyzed. The results of the diagnostic experiment confirming the connection between anxiety, self-esteem and experience of loneliness in adolescence are presented.